Stock Market Variability and Trading: 'Stock Power' a New Indicator for Profitable Trading - Mittal , A.K.; Aggarwal, Vimal K. (Gyan Management Journal, 2013)
Stock market experiences variations so rapidly and frequently that many of the market players like traders, speculators and investors use technical indicators to track the stock movements, analyze the generated patterns and charts; and conclude the buying and selling signals. There are numerous varieties of technical indicators available like daily moving averages, ROC, RSI, MACD etc. but these indicators are developed on stock prices only. Trading volume is not part of these indicators and considered separately, if desired by analysts. Trading Volume being equally important parameter and its impact cannot be ignored/ram analysis. A new indicator, named STOCK POWER (SP) is developed and presented in this paper. 'Stock power' indicator takes the stock price variability into account along with due influences of tading volume and generate the buying/selling signals. Analysis of several securities/ram different sectors has been tested with SP indicator and results are found reliable.
Keywords: Stock Power indicator; Stock variability; impact; Volume factor